Haikyu!! 42, Becoming - Furudate, Haruichi, 1983- (Shonen Jump manga., 2021)
"Hinata is removed from the game with a fever, leaving Karasuno to battle it out with Kamomedai in the final set without their biggest scorer! Distraught at not being able to be there for his teammates, Hinata watches the rest of the game via broadcast. What does he see from the outside of the court? The Spring Tournament arc comes to an end!"--